ANALISIS TINGKAT MATH ANXIETY DALAM PEMBELAJARAN MATEMATIKA SISWA SEKOLAH DASAR DI MASA PANDEMI COVID-19 - Sri Sugiarti; Kusmayanti, Intan (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
During the covid-19 pandemic, students in Indonesia conduct online learning from home as an effort to socially distancing. Mathematics anxiety is tension, a force that interferes with students in solving problems contained in math problems. This study aims to describe students' math anxiety in the covid-19 era and find solutions to overcome math anxiety. The research method used is descriptive quantitative. The instrument used in this study was a questionnaire using the Guttman scale type with two alternative choices, namely Yes and No for students' mathematics anxiety. Based on the results of the study, it was found that the category of students' mathematics anxiety level (low, medium, high) with the majority of students being in the medium category of mathematics anxiety.